Problems of modern diagnostics of choledocholithiasis - S. G. Shapoval’yants; T. B. Ardasenov; D. A. Freydovich; A. G. Mylnikov; A. G. Pan’kov; S. A. Budzinsky; A. A. Nikonov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
The aim of review. To discuss issues of diagnostics of choledocholithiasis at the present time.Original positions. The relevance of early recognition of choledocholithiasis is determined by high frequency at patients with cholelithiasis and risk of development of life-threatening complications. Diagnostics of choledocholithiasis is based on clinical data, laboratory and instrumental tests. Instrumental methods of investigation differ by their information value and invasiveness. So, it is important to define prognostic criteria (clinical, biochemical and ultrasound), determining necessity of additional more invasive and expensive investigation of bile ducts. However estimation of diagnostic criteria suggested by different authors and their threshold values is ambiguous. Discordant opinions frequently lead both to underestimation of the role of clinical and laboratory data, and to unjustified application of invasive diagnostic methods.Conclusion. Further studies are necessary to develop more rational and objective systems of diagnostics of choledocholithiasis.